2005
DOI: 10.1007/bf03030588
|View full text |Cite
|
Sign up to set email alerts
|

Altered physiology in trehalose-producing transgenic tobacco plants: Enhanced tolerance to drought and salinity stresses

Abstract: Transgenic tobacco (Nicotiana tabacum L. var. SR1) plants that over-express the Escherichia coli trehalose-6-phosphate synthase (TPS) gene (otsA) synthesized small amounts of trehalose (<400 pg gl leaf) while non-transformants produced no detectable trehalose. Some transgenic plants expressing a high level of otsA exhibited stunted growth and morphologically altered leaves. We tested F2 homozygous plants devoid of phenotypic changes to determine their physiological responses to dehydration and salinity stresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Thus, trehalose allows plants to tolerate naturally occurring stress during the period of dehydration and rehydration (Drennan et al 1993). Transgenic tobacco plants expressing TPS or otsA gene were shown the enhancing of dehydration tolerance (Romero et al 1997), and trehalose-producing tobacco plants showed enhanced tolerance to drought and salinity stresses (Jun et al 2005). Similar results were also reported in transgenic rice plants increases trehalose accumulation and abiotic stresses tolerance (Jang et al 2003;Garg et al 2002).…”
Section: Introductionsupporting
confidence: 54%
“…Thus, trehalose allows plants to tolerate naturally occurring stress during the period of dehydration and rehydration (Drennan et al 1993). Transgenic tobacco plants expressing TPS or otsA gene were shown the enhancing of dehydration tolerance (Romero et al 1997), and trehalose-producing tobacco plants showed enhanced tolerance to drought and salinity stresses (Jun et al 2005). Similar results were also reported in transgenic rice plants increases trehalose accumulation and abiotic stresses tolerance (Jang et al 2003;Garg et al 2002).…”
Section: Introductionsupporting
confidence: 54%
“…proline, inositol, raffinose, galactinol, and trehalose, was also reported (Schafleitner et al, 2007;Vasquez-Robinet et al, 2008;Evers et al, 2010;Legay et al, 2011;Kondrak et al, 2012). The overexpression of genes involved in Pro and trehalose biosynthesis also enhanced drought tolerance in several crops (Garg et al 2002;de Ronde et al 2004;Cortina & Culianez-Macia 2005;Jun et al 2005). Sugars including raffinose are also important in controlling ROS production during drought stress (Pelleschi et al 1997).…”
Section: Introductionmentioning
confidence: 69%
“…Pleiotropic effects resulting in developmental abnormalities due to constitutive expression of these genes have been reported in tobacco, potato and tomato (Cortina and Culianez-Macia 2005; Jun et al 2005; Yeo et al 2000). T6P may be responsible for these effects because engineering strategies that minimize free T6P concentrations report the absence of negative pleiotropic effects.…”
Section: Introductionmentioning
confidence: 99%